Unidades de relevo em zona costeira estuarina: municípios de Colares e Santo Antônio do Tauá - BARBOSA, Estêvão José da Silva (Universidade Federal do Pará, 2014)
This work identified and argued the geomorphic units (relief) of Colares and Santo Antônio do Tauá municipalities, State of Pará, Brazil. It has Geomorphology as subject. The studied area is located in eastern portion of Amazon River Estuary (“Golfão Marajoara”), northeast of Marajó bay, at estuarine coastal zone. In this study was used: bibliography, maps, remote sensing data and work fields. The analysis was made by two scales. First Scale is represented by the Amazonian Coastal Zone, which shows low altitude, sedimentary lithology, macrotidal tidal range, tropical and wet climate and stronger river discharges. This regional coast was produced by relative sea-level fluctuations, climatic changes, and tectonic dynamics occurred throughout Late Cenozoic. Eastern portion of Amazon River estuary is formed by Pará River Estuary – Marajó Bay, a typical tidal river or river-dominated estuary, although it has tidal influence. River discharge is main component of the estuarine dynamics, sedimentary constitution and biota organization. Pará River Estuary is a coastal environment with less energy of waves and littoral currents than the shore of Northeast Pará. In the second scale, were identified eight geomorphic units: sandy estuarine channel; tidal mud bank; tidal mud flat; estuarine beach; dune-beach ridge; tidal influence alluvial plain; alluvial plain; plateau. Only plateau is a erosive relief unit. The research also deals spatial distribution of these geomorphic units, in two sectors. Sector 1 is located in western portion of studied area. It is largely influenced by tides, and has different depositional relief units. The major geomorphic unit is tidal influence alluvial plain, which results of transition between marine and alluvial factors. Freshweater swampy formations followed mangroves toward landward due to reduced saline influence in the channels. Sedimentary distribution is marked by sand bottom channels, and mud deposits in the margins. Beachs are shorts, commonly covered by mud sets because less wave energy and crucial role of tidal current, discharges action in the coastal dynamics. Dune-beach ridges localized landward coastal plain are the indicative its progression. In this sector, plateaus are discontinuous due to erosion and deposition by tidal, flow channels and rains. Sector 2, localized in eastern portion of studied area, has no tidal influence. It shows a relief little compartmented, with large plateaus dissected by rivers. Fluvial action formed valleys with narrow alluvial plains, which demonstrated a greatest erosive surface in the sector 2.